2021
DOI: 10.1002/asia.202100151
|View full text |Cite
|
Sign up to set email alerts
|

Late‐Stage Alkylation of Heterocycles Using N‐(Acyloxy)phthalimides

Abstract: Synthetic methods enabling late-stage modification of heterocycles hold tremendous importance in the pharmaceutical and agrochemical industry and drug discovery. Accordingly, efficient, functional group tolerant and selective late-stage alkylation of valuable molecular entities is of enormous significance and well-acknowledged in medicinal chemistry. Radical alkylation of heteroarenes employing carboxylic acids as the alkyl radical precursor represents one of the most direct ways of CÀ H functionalizations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…The high regioselectivity observed across the scope highlights the advantage of this protocol over those operating via RPC scenario. 199 In 2018, the groups of Shang and Fu described the use of RAEs 74.1 as a source of alkyl radical 213,214 to produce desaturation products 74.2 upon β-H loss. 215 A dual ligand system was found to be crucial, as much lower yield was obtained without CyJohnPhos.…”
Section: C−h Arylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The high regioselectivity observed across the scope highlights the advantage of this protocol over those operating via RPC scenario. 199 In 2018, the groups of Shang and Fu described the use of RAEs 74.1 as a source of alkyl radical 213,214 to produce desaturation products 74.2 upon β-H loss. 215 A dual ligand system was found to be crucial, as much lower yield was obtained without CyJohnPhos.…”
Section: C−h Arylationmentioning
confidence: 99%
“…In 2018, the groups of Shang and Fu described the use of RAEs 74.1 as a source of alkyl radical , to produce desaturation products 74.2 upon β-H loss . A dual ligand system was found to be crucial, as much lower yield was obtained without CyJohnPhos.…”
Section: Palladiummentioning
confidence: 99%
“…Recently, the readily available N ‐(acyloxy)phthalimides (NHPI esters) have emerged as a potent source of alkyl radicals under photochemical conditions [23] . The redox chemistry of NHPI esters have been successfully applied in an array of carbon‐carbon bond formation, and late‐stage functionalization of heterocycles and bioactive compounds [2c,24] . In 2018, Sherwood and co‐workers described a visible‐light organophotoredox‐catalyzed mono‐ and dialkylation of various heteroarenes 31 and elaborated the technique for the late‐stage functionalization of several drugs or drug‐like candidates (Scheme 7, condition A) [25] .…”
Section: Functionalization Via C−c Bond Formationmentioning
confidence: 99%
“…However, the chemo‐ and stereoselective functionalization at targeted sites of advanced molecular entities at a late‐stage rather than an early stage of a synthetic campaign still remains an uphill task and is highly demanded in medicinal chemistry and drug discovery [2d,4] . Furthermore, the employed reaction technologies allowing late‐stage functionalization (LSF) of advanced synthetic intermediates, APIs (active pharmaceutical ingredient) or functional materials ought to be milder, considering the presence of a variety of potentially non‐innocent functional groups on such molecular frameworks [2a,c,4b,5] …”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies from Okada and Odo revealed their propensity to undergo one-electron reduction, followed by N–O bond fragmentation to release alkyl radicals following decarboxylation . This reactivity underpinned the development of decarboxylative additions to olefins, arenes, and alkynes, as well as decarboxylative borylation, olefination, and cross-coupling. Aryl N -(acyloxy)­phthalimides have been exploited in decarboxylative borylation reactions, but the decreased stability of aryl radicals, relative to alkyl radicals, hinders decarboxylative processes. For example, aryl phthalimide esters provided a source of benzoyl esters in a Ni-catalyzed oxidation of aryl zinc reagents .…”
mentioning
confidence: 99%